Isolation and Characterization of Pathogenic Microbes Origin in Strawberry (Fragaria sp.) Based on Koch's Postulates - Asharo, Rizal Koen; Indrayanti, Reni; Damayanti, Aldira Putri; Putri, Hilda Arsyah Eka; Nabilah, Saskia; Pasaribu, Pinta Omas (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2022)
Strawberry (Fragaria sp.) is a horticultural plant originating from the Americas. Strawberries have a distinctive sweet and refreshing taste, and contain lots of vitamins and antioxidants that are useful for body health. But strawberries are also easily damaged. This damage can be caused by spoilage microorganisms such as bacteria and fungi that can grow if conditions permit such as the presence of appropriate temperature and humidity conditions. In this experiment, aims to isolate pathogenic microorganisms that cause disease in symptomatic strawberries and prove that these pathogens actually cause disease using Koch's Postulates method and then descriptive analysis is carried out. From the experimental results, it was found that soft rot disease in strawberries was characterized by rotten fruit parts that looked wet, slightly brownish in color, slimy, there were fine white threads and emitted a foul odor with a percentage of IP (disease occurrence) of 100% and KP (disease severity) of 92.66% where based on the score the damage was the highest.